The answer would be c.127
Answer:
45 because 7 x 9 = 63 so you have to do 5 x 9 = 45
Step-by-step explanation:
Answer:
i hated iready xD the answer should be 2
Step-by-step explanation:
if you use ride over run the rise would be 2 and the run is 1
= 2
Answer:
Mean = 24
Variance = 107.78
Standard deviation = 10.38
Hope this helps! :)
Answer:
![(f\circ h)(2)=2](https://tex.z-dn.net/?f=%28f%5Ccirc%20h%29%282%29%3D2)
Step-by-step explanation:
<u>Composite Function
</u>
Given f(x) and h(x) real functions, the composite function named
is defined as:
![(f\circ h)(x)=f(h(x))](https://tex.z-dn.net/?f=%28f%5Ccirc%20h%29%28x%29%3Df%28h%28x%29%29)
It can be found by substituting h into f.
We are given the functions:
![f(x)=2x^2-9x+2](https://tex.z-dn.net/?f=f%28x%29%3D2x%5E2-9x%2B2)
![h(x)=x^2-4](https://tex.z-dn.net/?f=h%28x%29%3Dx%5E2-4)
It's required to find ![(f\circ h)(2)](https://tex.z-dn.net/?f=%28f%5Ccirc%20h%29%282%29)
As defined above:
![(f\circ h)(x)=f(h(x))](https://tex.z-dn.net/?f=%28f%5Ccirc%20h%29%28x%29%3Df%28h%28x%29%29)
Thus:
![(f\circ h)(2)=f(h(2))](https://tex.z-dn.net/?f=%28f%5Ccirc%20h%29%282%29%3Df%28h%282%29%29)
Find h(2):
![h(2)=2^2-4=0](https://tex.z-dn.net/?f=h%282%29%3D2%5E2-4%3D0)
h(2)=0
Now:
![(f\circ h)(2)=2(0)^2-9(0)+2](https://tex.z-dn.net/?f=%28f%5Ccirc%20h%29%282%29%3D2%280%29%5E2-9%280%29%2B2)
![(f\circ h)(2)=2](https://tex.z-dn.net/?f=%28f%5Ccirc%20h%29%282%29%3D2)